Nadal Critical and Ride Index Characteristics of Inspection Train Using Universal Mechanism Software on Different Back to Back - utomo, Ilham Satrio; Atmaja, Dadang Sanjaya; Febrilian, Benecdiktus Ergo (Nusantara Publisher, 2024)
This research conducted dynamic simulations using the Universal Mechanism software with variations between back to back widths of 1000 mm and 990 mm, focusing on the relationship between train operating speed, vibration levels, and passenger comfort index during operation on a small curve on the PPI Madiun track with a radius of R42. The issue investigated in this study stems from PM No. 17 of 2011, which sets the standard back-to-back usage at 1000 mm. It is crucial to understand the characteristics of each back to back setting, as the operational track gauge used is 1067 mm. The simulation results indicate that the nadal criterion and ride index are more favorable with the 990 mm back to back setting. At a speed of 25 km/h, the nadal criterion for the 990 mm setting was 0.636, compared to 0.670 for the 1000 mm setting, and the ride index for the 990 mm setting at this speed was 1.315449, compared to 1.288552 for the 1000 mm setting. These results are considered valid as the error value in the data validation calculations was less than 10%, specifically 8.26%.